Conservation biology of Colchicum autumnale L. and Campanula trachelium L. in the Nore Valley, Southeast Ireland - Smith, Rhian Jane (Trinity College (Dublin, Ireland). Department of Botany, 2004)
The conservation of plant biodiversity can only proceed effectively if it is informed by a detailed biological knowledge of the target species and their constituent populations. The overall aim of this study was to assess the Irish conservation status of Colchicum autumnale and Campanula trachelium in the Nore Valley through the collection, analysis and review of population data relevant to the survival of the species in Ireland. Demography and reproductive biology were investigated using permanent quadrats or by randomly sampling the populations. Genetic diversity within and between populations was investigated using the AFLP DNA fingerprinting technique.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin